A study of antioxidant protection in fluoride induced rat kidney lysosomal damage - Arhima, Mahmud H (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Pharmacology & Therapeutics, 2005)
Fluoride as an inorganic chemical species is ubiquitous in our environment. Fluorosis is a disease or state of chronic poisoning from long-term exposure to excessive quantities of inorganic compounds of fluorine and is a serious health problem in some countries, which is attracting the attention of the World Regulatory Agencies. Epidemiologically, the risk of fluorosis is now well recognized all over the world with greater emphasis on environmental fluoride and its misuse in consumer items, particularly oral hygiene products. Excessive fluoride ingestion over a prolonged period can adversely influence many tissues and organs. Kidney is one of the main target organs attacked by excessive amount of fluoride. Fluoride has been shown to affect human as well as animal kidney structures and functions and increase NAG isozyme release in human and animals urine after renal cell lysosomal damage. The lysosomal membrane damage and the consequent lysosomal acid hydrolase(s) release have been shown to jeopardize cellular integrity and to cause cell apoptosis or necrosis. Increased generation of free radicals, enhanced lipid peroxidation and disturbed antioxidant defence systems have been proposed to mediate the pathogenesis of fluoride toxicity in tissues.
Keywords: Pharmacology & Therapeutics, Ph.D.; Ph.D. Trinity College Dublin